Survival Book to Help BIPA Learners Off the Hook of Culture Shock - Hespi Septiana; Him’mawan Adi Nugroho; Warsita Noer Ardiyanti; Masilva Raynox Mael; Agus Ridwan (Jurnal Lingua Idea, 2021)
From time to time, Indonesian for Foreign Speakers (BIPA) continues to grow, including BIPA at the State University of Surabaya (Unesa). It cannot be denied that in its journey, BIPA Unesa encountered various problems. One of them is a report from a foreign student who was confused when he first arrived in Surabaya. Their confusion includes finding the ideal place to live, using online motorcycle taxi applications, and using public facilities such as markets, hospitals, and police stations. Not only that, but the understanding of academic rules on campus has also not been able to be conveyed on target. Some local students and lecturers have helped, but the limited number and time have made it impossible to assist students. Therefore, this research focuses on making a pocketbook called "survival book" in five different languages ​​for foreign students. The benefits of this research are expected to be able to solve the concerns of BIPA students when they first come to Surabaya with the development of a pocketbook. This research belongs to the category of product development. With this research, it is hoped that it will produce an output in the form of a survival book for BIPA Unesa students as well as scientific articles that will be published in accredited national journals.